Species of Thripinae (Thysanoptera) from bamboo in Malaysia, with one new species and six new records - Ng, Y.f.; Mound, L. A. (Zootaxa, 2015)
Nine species of Thripinae that inhabit bamboo are recorded from Malaysia. Clypeothrips idrisi sp.n. is described as a second species in the genus, and Trichromothrips bruncurrum Reyes is considered a syn.n. of Neocorynothrips asiaticus Ramakrishna & Margabandhu. Six species are newly recorded from Malaysia: N. asiaticus, Okajimaella tubercula, Simulothrips banpoti, Stenchaetothrips bambusicola, S. bambusae and S. spinalis. Seven species of Stenchaetothrips are now known from Malaysia. Illustrations and descriptions of each species are provided.